WHY ARE WRITTEN COMMUNICATION SKILLS IMPORTANT FOR BUSINESS STUDENTS? - Kowalewski, Susan; Halasz, Magdalene E. (Archives of Business Research, 2019)
Notwithstanding the availability of business writing instruction in academia, employers continue to voice their concerns about the significant gap between their expectations for employees’ writing skills and the actual skills employees possess (Lentz, 2013). Organizations are reporting lower levels than “meet expectations” related to employees’ written communication skills at the time an employee is hired (Suvedi, M., Ghimire, R.P., & Millenbach, K.F., 2016). Consequently, employers spend a considerable amount on remedial training to address the poor writing skills among their employees (White, A.V., 2015). Employers expect that written communication skills are taught in college. Data demonstrates, however, that this is not occurring or at least not to the level of competence that employers are seeking (Carnes, L., Awang, F., & Smith, H., 2015). Colleges and universities need to evaluate their curriculum and outcomes; integrating new initiatives into the curricula and programs to improve the written communication skills of their students.